THE ROLE OF THE MEDIA IN CREATING A NARRATIVE OF MUSLIM AND CHRISTIAN HARMONY THROUGH THE VALUES OF DALIHAN NA TOLU - Godlif Sianipar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to analyze the role of local media in North Sumatra in creating a narrative of harmony between Muslims and Christians through the integration of Dalihan Na Tolu values, a local wisdom of the Batak community. The research method used is qualitative with data collection techniques through interviews, observations, and documentation analysis of local media. The results of the study show that the media has a significant influence in building a positive narrative that encourages cooperation between religious communities. News that highlights mutual cooperation, mutual respect, and togetherness in social activities is the central theme carried by the media to create a harmonious atmosphere. The values of Dalihan Na Tolu—consisting of Somba Marhula-hula (respecting the elders), Elek Marboru (helping the younger), and Manat Mardongan Tubu (being careful of others)—are used to strengthen the narrative of harmony carried. Although the media faces several obstacles, such as political pressure and limited resources, they still try to present neutral and constructive news. The positive response from the community and religious leaders shows that media reporting based on local values is effective in reducing tensions and increasing social solidarity. The conclusion of this study emphasizes that local media has a strategic role in building harmony between religious communities through the local wisdom approach, which can be used as a model to manage diversity in a multicultural society.